2008
DOI: 10.1111/j.1744-7348.2008.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Cropping system influences Tomato spotted wilt virus disease development, thrips population and yield of tomato (Lycopersicon esculentum)

Abstract: Yield of tomato is limited by many diseases including Tomato spotted wilt virus disease. This study was conducted in the field at Kenya Agriculture Research Institute Njoro, Kenya, in 2004 and 2006 to determine the effect of intercropping on disease development, thrips population and yield of tomato variety Cal J grown under four intercrop systems involving kale, onion, maize and sole tomato. The experimental design was a Randomised Complete Block Design (RCBD) replicated three times. Disease scores on tomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have reported inconsistent intercropping effects on tomato yields, which were unaffected by intercropping with kale, onion, and lettuce but reduced by intercropping with maize and garlic (Liu et al, 2014;Ramkat et al, 2008). The negative intercropping effects on the yields may be partly related to synchronization of maximum requirements for growth resources by the intercropped species (Fukai and Trenbath, 1993).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have reported inconsistent intercropping effects on tomato yields, which were unaffected by intercropping with kale, onion, and lettuce but reduced by intercropping with maize and garlic (Liu et al, 2014;Ramkat et al, 2008). The negative intercropping effects on the yields may be partly related to synchronization of maximum requirements for growth resources by the intercropped species (Fukai and Trenbath, 1993).…”
Section: Resultsmentioning
confidence: 93%
“…In previous studies, the intercropping effects on tomato yield varied with different intercropped crops. In a field production trial performed in Kenya, intercropping tomato with onion and kale did not reduce marketable tomato yields compared with monocropping tomato; however, intercropping tomato with maize reduced the tomato yields, possibly due to the taller canopy of maize than other intercrops (Ramkat et al, 2008). In a tomato/garlic intercropping system using organic medium under plastic tunnels in China, intercropping reduced the total spring tomato yield than did monoculture of tomato, possibly due to its competition with garlic for nutrients and water (Liu et al, 2014).…”
mentioning
confidence: 91%
“…Cropping systems, on the other hand, are known to increase insect vector population and the emergence of MLN disease epidemics in maize. In intercropped versus mono-cropped systems, a significant number of assessment studies have demonstrated disease declines (Boudreau, 2013;Gopal et al, 2010;Ramkat et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Due to shade, this may have caused a sort of partial blockage of sunlight by the corn or watermelon leaves, thus making thrips feel at home in the plant chili. Different results when corn is intercropped with tomatoes, such as a journal article in [17] comparing four intercropping systems involving kale, onions, corn, and tomatoes, found that the thrips population was lower than other intercropping combinations only that the weight of the tomatoes produced was low.…”
Section: A the Average Number Of Thrips Infesting Red Chili Plantsmentioning
confidence: 99%